The Effectiveness of the Teams Games Tournament Learning Model Using QuARD Media to Improve Science Learning Outcomes - Nikmah, Putri Khoirotun; Ratnasari, Yuni; Masfuah, Siti (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
This research is motivated by the low learning outcomes of third-grade students in the subject of science at SD 2 Gondangmanis, mainly caused by the use of conventional learning models that do not actively involve students. To overcome this, the Teams Games Tournament learning model, incorporating QuARD media (Question and Action Cards), is applied. This model is designed to improve understanding of concepts and science process skills through educational games and group competitions. The purpose of this study is to analyze the differences in the average learning outcomes of students before and after the implementation of the Teams Games Tournament learning model assisted by QuARD media, and to determine the improvement in student learning outcomes after the intervention. This study employs a quantitative approach with a pre-experimental design, utilising a one-group pretest-posttest model. The subjects of the study were 22 third-grade students of SD 2 Gondangmanis. Data collection was conducted through interviews, observations, documentation, and written tests, including essays. Data analysis techniques include normality tests, paired sample t-tests, and N-Gain tests. The study's results showed a significant increase in student learning outcomes, with an average pretest score of 41.00 and a posttest score of 86.81. The t-test showed a significant difference between the pretest and posttest scores. The N-Gain value of 0.78 falls within the high category, and 96% of students achieved learning completion. It can be concluded that the Teams Games Tournament learning model, assisted by QuARD media, is effective in improving student learning outcomes in the science subject, particularly in understanding concepts and process skills.